An Analytical study of Government Scheme for Farmers in Gujarat: Impact, Implementation Challenges, and Policy Implications - Amitkumar Parsotambhai Thesiya; Dinesh C. Dhoniya (International Journal of Rural and Regional Development, 2026)
Gujarat’s economy is mostly dependent on agriculture, which increases food security, rural employment, and state revenue. Despite the state’s notable progress in irrigation infrastructure and agricultural commercialization, Gujarat farmers continue to face challenges, such as market volatility, water scarcity, unpredictable weather, and rising input costs. The governments of Gujarat and India have implemented several initiatives aimed at addressing these problems, including crop insurance, irrigation expansion, farm mechanization, income support, digital facilitation, and sustainable agricultural development This report critically evaluates the planning, execution, and results of significant government initiatives intended to assist Gujarat farmers. It assesses projects pertaining to risk reduction (crop insurance programs), financial inclusion (direct income assistance and credit facilities), irrigation (micro-irrigation and water conservation programs), and technology adoption (digital platforms and farm mechanization). The study also looks at how well these programs meet the various requirements of small and marginal farmers, who make up most parts of the agricultural sector. Key implementation problems are identified by the study, including farmer ignorance, administrative inefficiencies, benefit payout delays, and regional differences in program access. Additionally, it evaluates how institutional governance and coordination affect these projects’ success. The research offers a thorough grasp of the advantages and disadvantages of current policies by examining current literature, government papers, and policy documents. This paper provides policy recommendations to improve the efficacy, inclusiveness, and sustainability of agricultural projects using a descriptive and analytical methodology based on secondary data sources. The results are intended to promote Gujarat’s long-term agricultural growth and farmer welfare through better policy formulation and execution tactics.
Keywords: Agricultural policy; Gujarat agriculture; farmers welfare; government schemes; income support programs